IMPACTO DE LOS CICLONES TROPICALES DEL ATLÁNTICO EN AMÉRICA CENTRAL, TEMPORADA DE 1968 Y 1969 - Solano Chaves, Flora Julieta (2011)
In the years of 1968 and 1969, the hurricane season was very active near the Caribbean coast of Costa Rica; however, at present there are not studies of the impact of these systems over the different socioeconomic sector affected. For this reason, this paper analyze the presence and impact of these phenomena, in the years of 1968 and 1969, over some Caribbean Islands, Mexico and the United States, emphasizing Costa Rican territory. Respect to 1968, the study and analysis focus is the hurricane Gladys (October 16-21). In the 1969 season with the tropical cyclones Camille (August 14-16), Francelia (August 29 – September 4), Jenny (October 1-2) and Martha (November 21-25).